The effect of pomegranate extract on oxygen transport and exercise performance in highly trained cyclists at low and high altitudes - Crum, E.; Che Muhamed, M.; Stannard, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Maximal aerobic exercise performance is often limited by the rate of oxygen (O2) delivery via the erythrocytes to the muscles for energy production (Wagner, 1996). Nitric oxide (NO), produced endogenously by NO synthases in epithelia and also from dietary nitrate (NO3-), induces dilation of the arterioles, improving blood flow and reducing erythrocyte damage. Pre-exercise intake of NO3- rich beetroot juice (BJ), reduces O2 uptake (VO2) for the same submaximal cycling workload, leading to an improvement in power output at VO2max and time to exhaustion during a cycling time trial (TT) (Bailey et al. 2009; Lansley et al. 2011; Larsen et al. 2007). However, BJ has little such effect in highly-trained athletes who have greater vascular control. Pomegranate extract (POM) is high in NO3- and polyphenols; the latter increasing NO production in the stomach and protecting NO from oxidative damage (Ignarro et al. 2006). This study investigated whether POM reduces the O2 cost of exercise in highly-trained cyclists and if the effect is greater at high altitude where lower atmospheric O2 pressures impair O2 delivery to the muscles. Methods: Eight cyclists completed three stages of exercise at 50, 65 and 80% of their VO2max, followed by a TT to exhaustion (TTEX) at a workload calculated to elicit VO2max. The protocol was completed four times: at sea-level (SEA) and 1650m of altitude (ALT), with pre-exercise consumption of 1000mg of POM or a placebo (PL) at both altitudes. VO2 was measured in the last minute of each stage. A repeated measures ANOVA was performed for all dependent variables. Results: Maximal VO2 during the TT was significantly decreased in SEAPOM compared to SEAPL and increased in ALTPOM compared to ALTPL (p=0.022). Submaximal VO2 values were not affected. TTEX was reduced in ALT (p=0.01), but was not influenced by POM. Discussion: The improved O2 transport efficiency following POM allowed a similar TTEX with a lower maximal O2 cost at SEA, but POM enabled restoration of SEA VO2max values at ALT. Previous research has proposed that NO-induced vasodilation increases blood perfusion and O2 delivery to distal areas of myocytes, improving the matching of O2 delivery and requirement (Bailey et al. 2009). In POM, the combination of NO3- to produce NO and polyphenols to protect it, were effective in limiting the restrictions to O2 delivery in high altitude conditions.